The effects of evaporation time on morphological structure of polysulfone/cellulose acetate phthalate/polyvinylpyrrolidone (PSf/CAP/PVP) blend membranes - Ali, Asmadi (Trans Tech Publication, 2014)
Evaporation time is one of the important membrane fabrication parameter that can be manipulated in order to produce the desired membrane morphology in ultrafiltration (UF) separation process. The morphology of UF membrane has a significant effect on structural properties and performance of UF membrane. In this study, flat sheet asymmetric polysulfone/cellulose acetate phthalate/polyvinylpyrrolidone (PSf/CAP/PVP) blend membranes were prepared at different evaporation time in the range of 0 to 20 s to investigate its effect on the morphological structures of the blend membranes. The morphological structure of these blend membranes were characterized by using Scanning Electron Microscopy (SEM). The results showed that in the absence of evaporation time, the morphology of blend membrane consits of open finger-like structure and microvoids. Introduction of evaporation time period between 5 to 10 s, produced spongy blend membranes with less finger-like structure. Further increment of evaporation time between 15 to 20s, formed incomplete dense structure with small microvoids PSf/CAP/PVP blend membranes.